Differences in surgical outcomes between cervical goiter and retrosternal goiter: an international, multicentric evaluation - Cappellacci, Federico; Canu, Gian Luigi; Rossi, Leonardo; De Palma, Andrea; Mavromati, Maria; Kuczma, Paulina; Di Filippo, Giacomo; Morelli, Eleonora; Demarchi, Marco Stefano; Brazzarola, Paolo; Materazzi, Gabriele; Calò, Pietro Giorgio; et al. (Frontiers in Surgery, 2024)
Goiter is a common problem in clinical practice, representing a large part of clinical evaluations for thyroid disease. It tends to grow slowly and progressively over several years, eventually occupying the thoracic inlet with its lower portion, defining the situation known as retrosternal goiter.Total thyroidectomy is a standardized procedure that represents the treatment of choice for all retrosternal goiters, but when is performed for such disease, a higher risk of postoperative morbidity is variously reported in the literature. The aims of our study were to compare the perioperative and postoperative outcomes in patients with cervical goiters and retrosternal goiters undergoing total thyroidectomy. In our retrospective, multicentric evaluation we included 4467 patients, divided into two groups based on the presence of retrosternal goiter (group A) or the presence of a classical cervical goiter (group B). We found statistically significant differences in terms of transient hypoparathyroidism (19.9% in group A vs 9.4% in group B, p < 0.001) and permanent hypoparathyroidism (3.3% in group A vs 1.6% in group B, p = 0.035). We found no differences in terms of transient RNLI between group A and group B, while the occurrence of permanent RLNI was higher in group A compared to group B (1.4% in group A vs 0.4 % in group B, p = 0.037). Moreover, no differences in terms of unilateral RLNI were found, while bilateral RLNI rate was higher in group A compared to group B (1.1% in group A vs 0.1% in group B, p = 0.015). Wound infection rate was higher in group A compared to group B (1.4 % in group A vs 0.2 % in group B, p = 0.006).Based on our data, thyroid surgery for retrosternal goiter represents a challenging procedure even for highly experienced surgeons, with an increased rate of some classical thyroid surgery complications. Referral of these patients to a high-volume center is mandatory. Also, intraoperative nerve monitoring (IONM) usage in these patients is advisable.